A spiral-based inspection path generation algorithm for efficient five-axis sweep scanning of freeform surfaces. (July 2020) - Chen, Lufeng; Zhang, Rong; Tang, Kai; Hu, Pengcheng; Zhao, Pengyu; Li, Zhaoyu; Han, Zhenwei
Abstract: Traditional inspection of freeform surfaces via three-axis or three ＋ two-axis CMM mainly works in a point-by-point manner where for each inspection point, the stylus of CMM has to approach to and then retract from the surface of inspection, which inevitably drags down (often substantially) the inspection efficiency. Recently, a new inspection apparatus called five-axis inspection machine has emerged, on which the stylus tip can continuously sweep on the part surface and the inspection efficiency can thus be tremendously improved. The crux in using this new inspection technology is how to plan an efficient five-axis inspection path (including both the position and orientation of the stylus). In this paper, we present a new type of five-axis inspection path generation strategy for the inspection of a general freeform surface. Based on the proposed index called Surface Sweep Rate (SSR), an algorithm is designed to partition the surface into a single spiral strip, which maximizes the overall SSR. Then, for this single spiral strip, a five-axis inspection path is generated that takes into consideration the key constraints such as the required smoothness of the probe head trajectory, the sampling density, and the collision-free condition. Physical inspection experiments of our proposed strategy are conducted on two typical freeform surfaces, and the results convincingly confirm the feasibility, effectiveness, and advantages of our new solution. Graphical abstract: Highlights: An inspection efficiency indicator called the Surface Sweeping Rate (SSR) is introduced for the five-axis inspection. A method based on SSR is presented to partition the free-form surface into a single spiral-like circular patch. An inspection path generation paradigm is presented to improve the smoothness of the head trajectory and guarantee the interference-free. Experiments verify the superior efficiency of our method over the conventional inspection methods.